1993
DOI: 10.1038/npp.1993.32
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Uptake Sites and Serotonin Receptors Are Altered in the Limbic System of Schizophrenics

Abstract: Serotonin (5-HT) uptake sites were mapped by autoradiographic means with PH]cyano-imipramine , the 5-HTIA receptor with [3HJ8-hydroxy-2-[di-n-propyl-amino]tetralin ([3HJ8-0H-DPAT), and the 5-HTz receptor with both pH]ketanserin and {l251]1ysergic acid diethylamide ([lZ5IJLSD) in eight nonneurologic controls and 10 cases with a diagnosis of schizophrenia. In the striatum, there was a marked heterogeneous patterning of 5-HT uptake sites that corresponded to the striosomallmatrix campartmentalization of the stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
142
3
7

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(166 citation statements)
references
References 47 publications
13
142
3
7
Order By: Relevance
“…Nevertheless, the present findings suggest that stimulation of 5-HT, presumably 5-HT 2 and 5-HT 1 receptors, can lead to an increase in striatal dopamine efflux which may contribute to the psychotomimetic effects of psilocybin. Of particular interest to the present study are indications that abnormalities in the number of 5-HT 1A and 5-HT 2A receptors have been found in the frontal cortex, nucleus accumbens, striatum, and hippocampi of schizophrenic patients (Mita et al 1986;Arora and Meltzer 1991;Joyce et al 1993;Laruelle et al 1993;Gurevich and Joyce 1997). Thus, the present data also support further evaluation of the 5-HT system in the pathophysiology of schizophrenia (Meltzer 1991).…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, the present findings suggest that stimulation of 5-HT, presumably 5-HT 2 and 5-HT 1 receptors, can lead to an increase in striatal dopamine efflux which may contribute to the psychotomimetic effects of psilocybin. Of particular interest to the present study are indications that abnormalities in the number of 5-HT 1A and 5-HT 2A receptors have been found in the frontal cortex, nucleus accumbens, striatum, and hippocampi of schizophrenic patients (Mita et al 1986;Arora and Meltzer 1991;Joyce et al 1993;Laruelle et al 1993;Gurevich and Joyce 1997). Thus, the present data also support further evaluation of the 5-HT system in the pathophysiology of schizophrenia (Meltzer 1991).…”
Section: Discussionsupporting
confidence: 75%
“…Two postmortem studies applying [ 3 H]cyano-imipramine and [ 3 H]paroxetine have initially shown that the density of SERT is decreased in the frontal cortex (Joyce et al, 1993;Laruelle et al, 1993a (Dean et al, 1995;Naylor et al, 1996;Gurevich and Joyce, 1997;Dean et al, 1999b). In fact, three of these studies did not report altered SERT densities but did find a decrease in the affinity of [ 3 H]paroxetine for SERT in hippocampal membranes, whereas the affinity of [ 3 H]paroxetine for SERT binding in the frontal cortex was unaltered (Dean et al, 1995Naylor et al, 1996).…”
Section: Serotonin Transporter (Sert)mentioning
confidence: 99%
“…Of note, atypical antipsychotics have high 5-HT 2 receptor antagonist properties, which is postulated to be a mechanism that confers the unique therapeutic profile of atypical antipsychotics (Meltzer 1992). Abnormalities of 5-HT 2 receptor expression have been demonstrated in schizophrenic brain, as well (Burnet et al 1996;Joyce et al 1993;Laruelle et al 1993). Taken together, these findings suggest that schizophrenia is associated with altered 5-HT 2 -like receptor activity in limbic structures.…”
mentioning
confidence: 91%
“…Although there are multiple serotonin receptors, psychotic symptoms are most likely associated with 5-HT 2 -like receptors (Meltzer 1992). 5-HT 2 receptors are localized in multiple limbic structures associated with schizophrenia, particularly in the hippocampus and nucleus accumbens (Joyce et al 1993). Agonists of 5-HT 2 receptors, such as lysergic acid, are psychotomimetic, and antipsychotics often have 5-HT 2 receptor antagonist properties.…”
mentioning
confidence: 99%